Design of fuel cell power system for hydrogen-powered inspection train used for overhead contact line equipment - LIU Chang; HUANG Yongcong; YIN Shu; TAO Shiyong; YANG Chunhua (机车电传动)
A 100 kW hydrogen energy power system based on proton exchange membrane fuel cells (PEMFC) was developed to meet the inspection trains for overhead contact line equipment along the railway lines under the jurisdiction of Xinshuo Railway Company, a subsidiary of CHN ENERGY Group. The system was designed to optimize the power supply voltage format and self-powering mode, enhance the system's adaptability to environmental temperatures, reduce system noise level, improve energy conversion efficiency, and enable communication and control between the fuel cell system, power distribution controller, and the train. The resulting product underwent verification on the performance and design indexes by a third-party testing organization according to national standards. Additionally, it was put into application on board to validate its compatibility with the train. The results show that the system fulfills the 700 V power supply requirements of the train, while the balance of plant (BOP) is self-powered without relying on external sources. The system can operate within a temperature range of -30 ℃ to 45 ℃, with noise emissions below 70 dB@0.3 m and a DC/DC converter efficiency rating of 40%. In practical applications, the fuel cell power system effectively helped the train in operations such as running, braking, and charging, demonstrating good compatibility with the train. The designed fuel cell power system successfully meets the requirements of the hydrogen-powered inspection train for overhead contact line equipment, providing a valuable design reference and practical engineering experience for the application of fuel cell power systems in railway transportation.